2023
DOI: 10.1097/mpg.0000000000003792
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-7 and Osteopontin Serum Levels as Biomarkers for Biliary Atresia

Abstract: Objectives: Matrix metallopeptidase-7 (MMP-7) and osteopontin (OPN) are important components in the pathophysiology of fibrosis in biliary atresia (BA). There has been much recent interest in MMP-7 serum level in the diagnosis of BA. We aimed to assess the diagnostic accuracy and prognostic value of both MMP-7 and OPN in a Western BA study. Methods: Diagnostic value was assessed by comparison of serum MMP-7 and OPN levels in infants with BA and age-matched cholestatic controls. Prognostic value was assessed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…A recent study in the UK has shown that MMP-7 may also hold significance in the diagnosis of BA among Western patients. 38 However, we found the sensitivity of MMP-7 in the diagnosis of BA was much lower in Western studies than in Asian studies, and the cutoff value was much higher. In addition to the use of different ELISA kits, this may also reflect ethnic differences in BA.…”
Section: Mmp-7mentioning
confidence: 63%
See 1 more Smart Citation
“…A recent study in the UK has shown that MMP-7 may also hold significance in the diagnosis of BA among Western patients. 38 However, we found the sensitivity of MMP-7 in the diagnosis of BA was much lower in Western studies than in Asian studies, and the cutoff value was much higher. In addition to the use of different ELISA kits, this may also reflect ethnic differences in BA.…”
Section: Mmp-7mentioning
confidence: 63%
“…The results of some important clinical studies on MMP-7 from 2018 to 2023 are shown in Table 1. [31][32][33][34][35][36][37][38][39][40] According to the systematic review by He et al, 31 the sensitivity, specificity, and area under the curve of MMP-7 in the diagnosis of BA were 96%, 91%, and 0.9847, respectively. It is worth noting that the studies by Jiang et al 32 and Yang et al 33 were comparable, because they used the same enzyme-linked immunosorbent assay (ELISA) kit to detect serum MMP-7 concentration, both were conducted in China, and the median ages of the patients in the BA group were similar in the two studies.…”
Section: Mmp-7mentioning
confidence: 99%
“…They found the specificity and sensitivity of MMP-7 in the diagnoses of BA to be 68% and 93%, respectively, with a negative predictive value of 71% (27). They further conclude that MMP-7 may be helpful in the diagnosis of BA, but it is far from a new diagnostic "gold standard" (27). Surgical consultation may be delayed given the hesitancy from pediatric teams due to perceived morbidity of surgical intervention (28).…”
Section: Discussionmentioning
confidence: 99%
“…Aldeiri et al recently conducted a single center study at a referral hospital in the United Kingdom to better define the role of MMP-7 in the diagnoses of BA. They found the specificity and sensitivity of MMP-7 in the diagnoses of BA to be 68% and 93%, respectively, with a negative predictive value of 71% (27). They further conclude that MMP-7 may be helpful in the diagnosis of BA, but it is far from a new diagnostic “gold standard” (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation